Successful treatment of ulcerative bronchiolitis in a woman with refractory Mycobacterium intracellulare infection. (29th April 2015) - Egan, John Patrick; Seides, Benjamin J; Olivier, Kenneth N; Addrizzo-Harris, Doreen
Abstract : We present a case of a woman with medically refractory ulcerative colitis (UC) who developed severe bronchiectasis, bronchitis, bronchiolitis and Mycobacterium intracellulare (MAC) infection 2 years after total colectomy. Despite being on optimal therapy for her MAC and sterilising multiple consecutive sputum cultures, she remained highly symptomatic, and this led to further investigations that revealed the presence of UC-related airways disease. Addition of immunosuppressive therapy to her antimycobacterial treatment resulted in sustained and complete clinical remission of her disease. To our knowledge, this is the only case published in the literature that describes a case of successful treatment of concomitant UC-related pulmonary disease and symptomatic MAC.